Social Policy Evaluation on Social Welfare Improvement of Neglected Elderly - Yanuardi Yanuardi; Kurnia Nur Fitriana; Marita Ahdiyana (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2017)
The aims of this study was to evaluate the implementation results of social policies for the neglected elderly (LUT) in Yogyakarta. The research approach was qualitative descriptive technique using data analysis of primary and secondarydata obtained from interviews, focus group discussions, observation and documentary analysis. The data validation employs triangulation technique. The research results indicate that the implementation of social policies for the neglected elderly in DIY was not yet optimal that can be derived from, the number of LUT covered in the policy was still small in number, the quality of services provided to neglected elderly remains minimal, community involvement in taking care of the LUT is not yet maximized, and the policies specifically manage LUT was not yet available. These happen because first, the specificsocial policy towards LUT was not yet established, the existing policies remain partial and overlapping with the policy of poverty, so that the implementation was insensitive towards the neglected elderly. Second, the available funding andinfrastructure in both intra and extra nursing institutions were still diminutive compared to the total number of LUTs in DIY. Third, the number of human resources conducting the policy was still limited, moreover the qualified ones were few.